Here's the question you clicked on:
keeponbleeding
Confirm that f and g are inverses by showing that f(g(x)) = x and g(f(x)) = x.
f(x) = 2/x and g(x) = 2/x
f(g(x)) well if you had f(3) you would substitute 3 into where you find x so you have f(g(x)) so substitute g(x) where you find x in f(x) this means you are substituting the function g(x) into f(x)
\[\rm f(g(x)) = {2 \over \large {2 \over x}}\]and\[\rm g(f(x)) = {2 \over \large{2 \over x}}\]Simplify.
@ParthKohli PARTH YOU ARE ALIVE
@amorfide YA I AM BACK FROM THE DEAD
ummm x for both???
showing that f(g(x)) = x and g(f(x)) = x. that is exactly what you should get well done
thanks! (that was easier than I thought) ^^